OPTIMISASI PROSES PEMESINAN EDM WIRE CUT UNTUK MODUS GERAK SIRKULAR MENGGUNAKAN ALGORITMA GENETIK - Martowibowo, Sigit Yoewono; Adriansyah, Adriansyah (Mesin, 2007)
Electro Discharge Machining Wire Cut (EDM Wire Cut) is one of non-conventional machining process which is used by many manufacturer industries. Technology development demands this process can produce high quality product with good productivity. To fulfill this demand, optimization of machining processes that involves several variables can be done. When doing the optimization of machining condition, an algorithm using mathematical model is needed to calculate the optimum values of process variables. There are many optimization techniques and methods which can be chosen, one of them is Genetic Algorithm. In this research work, an implementation of Genetic Algorithm in machining process optimization is presented. As the optimization parameters, feed rate and surface roughness selected. Based on the above parameters and considering the capability of the existing EDM Wire Cut, five input parameters are determined with right combination, namely no load voltage, capacitor, on time, off time and servo voltage. The output has been compared to other optimization method and it appears that the Genetic Algorithm shows promising results and thus may be proposed as an alternative tool in machining process optimization.